A SYSTEMATIC REVIEW OF VISUAL INSTRUCTIONAL MATERIALS IN ISLAMIC EDUCATION: CHARACTERISTICS, CLASSIFICATION, AND COGNITIVE LOAD REDUCTION - Ahmad Hikam Mutha’aliin; Anisah Fitri Melenia; Hasan Basri; Reza Fahlefi; Muhammad Iqbal (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
This study addresses the pedagogical challenges in Islamic Religious Education (PAI), where abstract religious concepts are frequently taught using monotonous verbal methods or overly complex digital multimedia, leading to student cognitive overload. The research aims to synthesize the characteristics, classification, and effectiveness of purely visual instructional materials in PAI and formulate a conceptual design model based on cognitive load management. Employing a Systematic Literature Review (SLR) compliant with PRISMA 2020 guidelines, data were collected from multiple academic databases and evaluated using thematic analysis. The findings indicate that purely visual instructional materials serve as transformative pedagogical instruments, translating abstract dogmas into concrete representations and effectively minimizing extraneous cognitive load. Furthermore, these materials are taxonomically classified into four primary typologies requiring ontological alignment with specific PAI subjects: graphic media, projection media, printed visuals, and realia. Finally, the study proposes a conceptual model demonstrating that integrating high-quality graphic design with accurate religious content stimulates intrinsic motivation to learn and optimizes working memory capacity. This mechanism successfully accelerates the comprehension of complex abstract concepts while facilitating the internalization of values for students' religious character formation. Ultimately, optimizing purely visual instructional materials offers a highly focused, minimally distracting approach to enhancing PAI learning outcomes.